Pain as bad as you can imagine or extremely severe pain? A randomized controlled trial comparing two pain scale anchors - Amy L. Tin; Mia Austria; Gabriel Ogbennaya; Susan Chimonas; Paulin Andréll; Thomas M. Atkinson; Andrew J. Vickers; Sigrid V. Carlsson (SpringerOpen, 2023)
Abstract Background A common method of pain assessment is the numerical rating scale, where patients are asked to rate their pain on a scale from 0 to 10, where 0 is "no pain" and 10 is "pain as bad as you can imagine". We hypothesize such language is suboptimal as it involves a test of a cognitive skill, imagination, in the assessment of symptom severity. Methods We used a large-scale online research registry, ResearchMatch, to conduct a randomized controlled trial to compare the distributions of pain scores of two different pain scale anchors. We recruited adults located in the United States who reported a chronic pain problem (> 3 months) and were currently in pain. Participants were randomized in a 1:1 ratio to receive pain assessment based on a modified Brief Pain Inventory (BPI), where the anchor for a score of 10 was either "extremely severe pain", or the original BPI, with the anchor "pain as bad as you can imagine". Participants in both groups also answered additional questions about pain, other symptomatology and creativity. Results Data were obtained from 405 participants for the modified and 424 for the original BPI. Distribution of responses to pain questions were similar between groups (all p-values ≥ 0.12). We did not see evidence that the relationship between pain score and the anchor text differed based on self-perceived creativity (all interaction p-values ≥ 0.2). However, in the key analysis, correlations between current pain assessments and known correlates (fatigue, anxiety, depression, current pain compared to a typical day, pain compared to other people) were stronger for "extreme" vs. "imaginable" anchor text (p = 0.005). Conclusion Pain rating scales should utilize the modified anchor text "extremely severe pain" instead of "pain as bad as you can imagine". Further research should explore the effects of anchors for other symptoms.